Evaluating registration staff understanding of electronic medical record use - Nurnanik, Iis; Widiyanto, Wahyu Wijaya (Science Midwifery, 2025)
This study aimed to evaluate the understanding of registration staff regarding the use of Electronic Medical Records (EMR) at Puskesmas Bringin, a primary healthcare center in Semarang Regency. Despite the growing emphasis on digital transformation in health services, the success of EMR implementation largely depends on how well frontline staff comprehend and engage with the system. Using a qualitative descriptive method, data were collected through in-depth interviews and direct observations with selected registration officers. The findings revealed varying levels of understanding among staff, influenced by differences in digital literacy, training exposure, and system accessibility. Some staff demonstrated strong conceptual and operational knowledge of EMR, while others relied on peer support or manual records due to uncertainty in system navigation. Technical barriers and limited organizational support further impacted their ability to fully utilize EMR functions. The study concluded that improving staff understanding requires targeted training, user-friendly system design, and continuous mentoring. These efforts are essential to ensure the successful integration of EMR in primary healthcare services and to support better health data management at the grassroots level.